Teacher’s Technology Integration ELT Based on SAMR Model in Writing Skill - Dani Fathurohman Fathurohman; Andi Dian Rahmawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This study is aimed to know the technology categories integrated by the teacher and classify the teacher’s technology integration level. Descriptive qualitative is used to describe the result of this study. The data is collected through interview and observation at SMA N 1 SENTOLO. It is focused on the teaching of writing. the subject of this research were 2 teacher. The data were transformed into descriptive text and interviewed transcripts. The data analysis used reduction data, the data display, and conclusion drawing or verification. The data validation used triangulation of technique of collecting data and triangulation of source of data.The source of data taken from interview . Based on the result of finding and discussion, it is found that the teacher integrated more than four technology categories which are word processing, spreadsheet software, organizing and brainstorm, multimedia, and web resources. The teacher integrated those technologies in teaching listening, reading and writing skill. While the activities is analysed based on SAMR model to know the teacher’s technology integration .The result shows that the teacher is on the augmentation level in teaching writing skill, which the teacher uses word processing with additional functions like spell check, cut, and paste the documents. Therefore, the teacher is classified on passing the substitution level, because the teacher is on the augmentation level, which integrates technology as a direct tool substitute, with functional improvement.